2019
DOI: 10.1097/aud.0000000000000705
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Telomere Length and Hearing Status in Mid-Childhood and Midlife: Population-Based Cross-Sectional study

Abstract: Objectives: The purpose of this study is to determine if telomere length (a biomarker of aging) is associated with hearing acuity in mid-childhood and midlife. Design: The study was based on the population-based cross-sectional study within the Longitudinal Study of Australian Children with telomere length and audiometry data. We calculated high Fletcher Index (hFI, mean threshold of 1, 2, and 4 kHz), defining hearing loss as threshold >15 dB HL (bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Differences in the research objectives, definitions of hearing loss, and study design and methods may be the reasons for inconsistencies between the results of different studies. We further examined the different degrees of hearing loss by being sex-specific, especially for mild hearing loss (similar to that reported by Wang et al [16]), to identify the early associations between telomere length and lifetime risk of hearing loss. From our results (Figure 1), we believe that the reason for the inconsistencies in previous studies may be the differences in the proportions of populations with different degrees of hearing loss in these studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Differences in the research objectives, definitions of hearing loss, and study design and methods may be the reasons for inconsistencies between the results of different studies. We further examined the different degrees of hearing loss by being sex-specific, especially for mild hearing loss (similar to that reported by Wang et al [16]), to identify the early associations between telomere length and lifetime risk of hearing loss. From our results (Figure 1), we believe that the reason for the inconsistencies in previous studies may be the differences in the proportions of populations with different degrees of hearing loss in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, for the study of hearing loss and telomere length, three cross-sectional studies have assessed the association between RTL and the risk of hearing loss; two studies reported an inverse association [15,17], whereas one study reported null findings [16]. Differences in the research objectives, definitions of hearing loss, and study design and methods may be the reasons for inconsistencies between the results of different studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, the results of studies on the relationship between telomere length and hearing level are quite limited and inconsistent Wang et al, 2019;Zhang et al, 2020). One study showed that longer telomere length was negatively related to hearing loss in older adults .…”
Section: Introductionmentioning
confidence: 99%